Modeling System Test of English as a Foreign Language as a Web-Based Learning Media - Nasir, M; Hasyimi; Mahdi; Amru (IOP conference series. Materials Science and Engineering, 2019)
This modeling test is equipped by web-based and multimedia system perform to save time and cost in learning TOEFL. The purpose of this research is to design and build the TOEFL system application as a web-based learning media in TOEFLlearning and test. The research specific target is the TOEFL system that can be used as an ICT learning medium online software website for the developing of TOEFL learning. The method used is quantitative method that starts from literature study, interview, observation, data analysis, model and system design, making of the application and system testing. The simulation of Web-based TOEFL modeling has been simulated using PHP and MySQL programming languages. The conclusion of this research is a web-based TOEFL simulation as a medium of online software learning in website for the development of learning TOEFL. The random question system will be worked better if the type of questions provided more on the TOEFL simulation. On the simulation, the same participants will not get the same combination of tests on different tests. This TOEFL system capable to runsign inby user-level identification process first, so that the system access is well controlled. This application can only be accessed by users who have made the sign up process.